Determinants of nest box local recruitment and natal dispersal in a declining bird population. Issue 1 (15th November 2021) - Carle‐Pruneau, Esther; Bélisle, Marc; Pelletier, Fanie; Garant, Dany
Abstract : Recruitment and dispersal are important demographic rates and studying their determinants is particularly important in the current context of global anthropogenic perturbations. In birds, and especially for migratory species, assessing these rates is challenging because of the difficulties involved in tracking individuals beyond fledging. Here we assessed the determinants of nest box local recruitment and natal dispersal distances in a declining aerial insectivore, the tree swallow Tachycineta bicolor . We used a 16‐year dataset obtained from the long term monitoring of a population breeding within a 10 200‐km 2 study system located along a gradient of agricultural intensification in southern Québec, Canada. Yearly nest box local recruitment rates ranged there in between 1.0% and 3.2%. Heavier nestlings who fledged earlier were more likely to recruit. Natal dispersal distances were generally short (mean ± SD = 12.7 ± 13.8 km) in the study system and were influenced by different factors depending on sex. Females dispersed over shorter distances when conspecific occupancy on breeding site was high, while males dispersed farther in the presence of competing house sparrows Passer domesticus and when their mother was young. Selection of breeding locations appeared to take place at multiple scales and individuals recruited in sites with characteristics similar to their natal sites. Our results provide important information concerning the factors influencing nest box local recruitment and natal dispersal dynamics of this migratory species. These factors should be considered in conservation practices for this species in order to support production of recruits in habitats favorable to their survival.